Economy and commercial construction cycle in Malaysia - Aminah Md. Yusof 559506; Pasific Rim Real Estate Society (PRRES) Conference (7th : 2001 : Adelaide) 481375 (Skudai : Universiti Teknologi Malaysia, 2001)
36